Capitalizing on public goods provision for the management of fragile agricultural systems: differentiation in innovation capacity of land managers in the face of conflicting policy regimes - Pinto-Correia, Teresa (2012)
Transition theories suggest that there is a spatial, temporal and structural co-existence of several processes of transition from productivism to post-productivism going on in rural areas in multiple and complex combinations (Geels and Schot 2007; Wilson, 2007). Transition can be characterized as a shift from the formerly dominant production goals towards a more complex, contested, variable mix of production, consumption and protection goals This is particularly true for South European landscapes dominated by extensive agro-silvo-pastoral systems and small-scale mosaic farming, with a fragile agricultural sector which in some cases is just entering the productivist phase, let alone moving towards post-productivism (Pinto-Correia Pinto-Correia 2010; Robinson 2008), both in terms of discourse and management practices (Tilzey & Potter, 2008). However, these are landscapes increasingly valued by society due to their potential for providing public goods related with environmental quality, nature conservation, landscape character and cultural identity. This encourages new strategies for farm survival and new ways of managing the land (Marsden, 2003; van der Ploeg et al, 2009) – requiring a paradigm shift, at farm level but also in policy formulation and targeting. In this paper, the differentiation of land managers facing multiple transition trends, and their relation to the type of farm unit they are managing, will be addressed. The multiple combinations of the land manager profile with the land management he is adapting to his farm unit is addressed. The study is applied to a local area in Southern Portugal, the municipality of Montemor-o-Novo. The area is located partially within a Natura 2000 site due to the presence of a hilly area, Monfurado, and the dominance of a well maintained and diverse Montado (together with the Dehesa, the agro-silvo-pastoral system characteristic of Southern Iberia). But it is also at a cross road of emerging demands as residential and recreation area, due to the Montado landscape but also the proximity of the Metropolitan area of Lisbon (100 km). It is thus a landscape maintained through the extensive livestock production and combined forestry system, and supporting today a wide range of environmental and social public goods, which could therefore profit specifically from public policies promoting public services. The typology aims to tackle the position both of the manager and of the farm unit, in the multifunctionality spectrum. It show there are all possible combinations of land owners and land managements taking place, just in one municipality and only considering large scale farm units with extensive use. By that, it makes it possible to assess how land managers may adapt and make use of policy mechanisms, and how those can be targeted if the differentaion of situations existing is to be considered.